The "Flat Tax(es)" : Principles and Evidence - Varsano, Ricardo (IMF Working Papers; Working Paper ;, 2006)
One of the most striking tax developments in recent years, and one that continues to attract considerable attention, is the adoption by several countries of a form of "flat tax." Discussion of these quite radical reforms has been marked, however, more by assertion and rhetoric than by analysis and evidence. This paper reviews experience with the flat tax, seeking to redress the balance. It stresses that the flat taxes that have been adopted differ fundamentally, and that empirical evidence on their effects is very limited. This precludes simple generalization, but several lessons emerge: there is no sign of Laffer-type behavioral responses generating revenue increases from the tax cut elements of these reforms; their impact on compliance is theoretically ambiguous, but there is evidence for Russia that compliance did improve; the distributional effects of the flat taxes are not unambiguously regressive, and in some cases they may have increased progressivity, including through the impact on compliance; adoption of the flat tax has not resolved common challenges in taxing capital income; and it may have strengthened, not weakened, the automatic stabilizers. Looking forward, the question is not so much whether more countries will adopt a flat tax as whether those that have will move away from it.